Isolation and characterization of plant growth promoting actinobacteria, Amycolatopsis samaneae (AM75), from the rice rhizosphere in Mirza area, Assam, India - Ahmeda, Nizara; Ranjan Patgiri, Saranga (Academia Journal of Biology, 2025)
This study aimed to isolate plant growth promoting actinobacteria from the rhizosphere of rice. Rhizospheric soil samples were collected from the Aijung variety of rice in the Mirza area, Kamrup district, Assam, India. The isolate AM75 identified as Amycolatopsis samaneae, was characterized as gram positive and non-motile. It exhibited varied colony characteristics on different selective media. The isolate producesseveral enzymesincluding urease, nitrate reductase, lipase, catalase, and amylase but did notdemonstrate cellulase or gelatinaseactivity. Notably, isolate AM75 displayed various plant growth promoting activities such as siderophore activity, hydrogen cyanide (HCN) production, indole-3-acetic acid (IAA) production, and zinc solubilization, though it did not produce hydrogen sulfide (H2S) or solubilize phosphate. The optimal growth conditions for AM75 werepH 7.2, 30 ºC temperature, and NaCl 2.5% concentration. Additionally, AM75 exhibited inhibitory activity against the plant pathogens Erwinia chrysanthemi ATCC11660, Aspergillus niger ATCC6275, and Fusarium oxysporum ATCC62506. The isolatewas resistant to standard antibiotics, including Rifampcin, streptomycin, ampicillin, and nalidixic acid.